PS 04-05 EFFECT OF STRESS ON AUTONOMIC ACTIVITY AMONG FIRST YEAR MEDICAL STUDENTS. (September 2016) - Goel, Anju; Ghosh, Suparna; Dhar, Usha; Srivastav, Rani; Krisna, Bal
Abstract : Objective: Psychological stress is a risk factor for hypertension and coronary artery disease. The process by which stressful stimuli influence disease is multifactorial, interactive and individualistic. the objective of this study is to know whether examination stress produces significant changes in the sympathetic activity of the students. Design and Method: Forty healthy first year medical students of either gender in the age group of 18–21 were taken into study. They were divided into 2 groups - Males (n = 20) and females (n = 20) and examined twice during the study period. None of these students were suffering from major neuropsychiatric disorder known to effect the functioning of autonomic nervous system. Psychological evaluation at non stress (no examination period) and stress (examination period) was done using standardized stress reaction checklist (SRCL) and Sinha anxiety scale. Autonomic cardiac regulation was assessed by resting heart rate, baseline blood pressure, orthostatic tolerance test (30:15 ratio), controlled breathing test (E:I ratio) and Hands grip dynamometer. Results: We observed that overall stress score in female medical students was significantly raised (23.100 ± 10.93) as compared to males (17.00 ± 7.08) during first year professional examination. In the anxiety scores, a change from a mean level of 31.0 ± 14.5 to 33.5 ± 18.0 was observed. Stress induced changes in autonomic function test in medical students (n = 40) during examination viz baseline heart rate, blood pressure, 30:15 ratio and delta change in blood pressure during isometric hand grip exercise were significant (p < 0.05). In controlled breathing test (E:I ratio) changes were not significant. Conclusions: The changes were suggestive of tilt in resting autonomic balance towards increased sympathetic activity.